Neuromuscular blockade in patients with ARDS: a rapid practice guideline - Alhazzani, Waleed; Belley-Cote, E.; Møller, M. H.; Angus, D. C.; Papazian, L.; Arabi, Y. M.; Citerio, G.; Connolly, B.; Denehy, L.; Fox-Robichaud, A.; Hough, C. L.; Laake, J. H.; et al. (Intensive care medicine, 2020)
The aim of this Intensive Care Medicine Rapid Practice Guideline (ICM-RPG) is to formulate an evidence-based guidance for the use of neuromuscular blocking agents (NMBA) in adults with acute respiratory distress syndrome (ARDS). The panel comprised 20 international clinical experts from 12 countries, and 2 patient representatives. We adhered to the methodology for trustworthy clinical practice guidelines and followed a strict conflict of interest policy. We convened panelists through teleconferences and web-based discussions. Guideline experts from the guidelines in intensive care, development, and evaluation Group provided methodological support. Two content experts provided input and shared their expertise with the panel but did not participate in drafting the final recommendations. We followed the Grading of Recommendations Assessment, Development, and Evaluation approach to assess the certainty of evidence and grade recommendations and suggestions. We used the evidence to decision framework to generate recommendations. The panel provided input on guideline implementation and monitoring, and suggested future research priorities. The overall certainty in the evidence was low. The ICM-RPG panel issued one recommendation and two suggestions regarding the use of NMBAs in adults with ARDS. Current evidence does not support the early routine use of an NMBA infusion in adults with ARDS of any severity. It favours avoiding a continuous infusion of NMBA for patients who are ventilated using a lighter sedation strategy. However, for patients who require deep sedation to facilitate lung protective ventilation or prone positioning, and require neuromuscular blockade, an infusion of an NMBA for 48 h is a reasonable option.